Dual Multiphase Boost Converter Using Pi Controller with Texas Instruments Microcontroller - Abd Rahman, Nuratiqah; Zulkifli, Shamsul Aizam (Evolution in Electrical and Electronic Engineering, 2025)
This project focuses on the design and development of a dual multiphase boost converter that can regulate output voltage when the load changes. This system is created to solve common problems found in single-phase boost converters, such as low efficiency, poor voltage regulation, and unstable performance. By using two phases working together, the converter can share current more evenly and improve overall system stability. The converter is controlled by a Proportional Integral or PI controller, which is programmed on a Texas Instruments TMS320F28335 microcontroller. The controller adjusts the duty cycle in real time to keep the output voltage steady. The project starts with simulation in MATLAB Simulink to test how the converter works with and without the controller. Then, the controller code is developed using Code Composer Studio to communicate with the microcontroller. The hardware, including the converter circuit and gate drivers, is designed using Proteus software and built on a printed circuit board or PCB. Testing is done to check if the system performs well when connected to a load. With a fixed input of 5 volts, the converter successfully increased the voltage to around 10.8 volts with stable output. The results show that this converter works well in practice and can be used in systems that need reliable voltage control.